Differential heart rate variability and physiological responses associated with accumulated short- and long-term stress in rodents - Park, Sunghee E.; Park, Dajeong; Song, Kang-Il; Seong, Joon-Kyung; Chung, Seok; Youn, Inchan (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
In this study, we tested the hypothesis that chronic stress has cumulative effects over time on heart rate variability (HRV) and physiological responses in a rodent model of chronic mild stress. Rats were exposed to either shortterm (2 weeks) or long-term (4 weeks) stress, followed by a 1-week recovery period. Controls were normally housed rats that did not undergo the stress procedure. For electrocardiogram recordihgs, transmitters were implanted in all rats 10 days before the onset of the experiment to allow recover y from surgery. To investigate physiological responses, body weight, temperature, sucrose preference, and serum corticosterone levels were measured weekly. Rats exposed to both short-and long-terin stress showed significant reductions in body weight, which did not normalize after the recovery period. A significant difference was observed between short-and long-term stress groups in serum corticosterone levels, with long-term stress significantly increasing serum corticosterone levels, which remained elevated after the recovery period (P < 0.05). HRV analysis indicated that long-term stress significantly decreased time-domain indexes, whereas significantly increased frequency domain indexes were observed in the low-frequency range (0.1-1 Hz). These results may represent dysfunction in parasympathetic/vagal modulation with hyperactivation of the sympathetic nervous system after long-term exposures to stress. In addition, prolonged Q-to-T wave (QT) intervals were observed in rats exposed to long-term stress, which did not return to baseline levels after the recovery period. These findings are consistent with the view that chronic stress is associated with cardiac autonomic disorders and emphasize the importance of monitoring stress in our daily life since the effects of even mild stress may be cumulative. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: CHRONIC MILD STRESS; POWER SPECTRAL-ANALYSIS; BLOOD-PRESSURE; MENTAL STRESS; QT-INTERVAL; MODEL; DEPRESSION; ARRHYTHMIAS; ANXIETY